Effects of Algicidal Macrophyte Metabolites on Cyanobacteria, Microcystins, Other Plankton, and Fish in Microcosms - Svetlana Kurbatova; Nadezhda Berezina; Andrey Sharov; Ekaterina Chernova; Evgeny Kurashov; Yulia Krylova; Igor Yershov; Alexander Mavrin; Natalia Otyukova; Elena Borisovskaya; Roman Fedorov (Toxins, 2023)
To control harmful algae blooms (HABs), methods based on natural mechanisms are now required. We investigated the effects of an algicide derived from macrophyte metabolites, namely mixtures of gallic, tetradecanoic, heptanoic, and octanoic acids (1:1:1:1 mass ratio, a total concentration of 14 mg/L), on the biomass of cyanobacteria and other plankton and the production of microcystins under experimental conditions. Two types of microcosms have been created: simple (microalgae, cyanobacteria, and zooplankton) and complex (microalgae, cyanobacteria, zooplankton, and planktivorous fish). We observed the dynamics of the phytoplankton structure, the concentrations of microcystins and chlorophyll-a, hydrochemistry, and the status of zooplankton and fish in both types of microcosms with and without algicide for one month (from 19 July to 19 August 2021). The introduction of algicide caused changes in phytoplankton structure, a drop in cyanobacterial biomass, and a decrease in the total concentration of microcystins. Surprisingly, the contributions of the most toxic microcystins (LR form) were higher in both types of microcosms exposed to algicide than in microcosms without algicide. The inhibitory effect on the cyanobacterial biomass was most significant in complex ecosystems (containing fish), while it was only observed at the end of the exposure in simple ecosystems. Not only algicide but also phytoplankton consumed by fish and zooplankton, as well as nutrient excretory activity by both consumers, seem to have impact on cyanobacterial biomass. This study found that the using chemical substances similar to macrophyte metabolites can help regulate HABs and cyanotoxins. However, the results differ depending on ecosystem type.